DIFFERENCES IN SYMPTOMS OF MEN AND WOMEN TEMPOROMANDIBULAR JOINT DISORDERS IN STUDENTS OF MEDICAL FACULTY UNIVERSITAS JENDERAL ACHMAD YANI BATCH 2020 - Azkya Patria Nawawi; Florence Meliawaty; Vivin Wijami Putri (Journal of Health and Dental Sciences, 2022)
Temporomandibular joint disorders (TMD) become one of the most common muscles and jaw problems in the population aged 20-40. TMD has a higher prevalence in women than men with a ratio between 3-4: 1 because gender is the most related risk factor in TMD. This study aims to determine the symptoms of TMD based on gender in students of the Faculty of Medicine of Universitas Jenderal Achmad Yani, batch 2020. The research used an analytical study using the cross-sectional method. The data were analyzed using a chi-square test with 152 research subjects. The results found that 50.7% of students experienced symptoms of TMD, whereas male students experienced TMD more often (53.2%) than females (49.5%), with a value of p = 0.727. In this study, there was no relationship between the symptoms of temporomandibular joint disorder and gender. DOI : 10.54052/jhds.sd22.p123-132